Alat-alat angkutan tradisionil di Kerinci - Nazir, M., B.A (Proyek Rehabilitasi dan Perluasan Museum Jambi, Kanwil Dep. P & K Prop. Jambi, 1979)
Brief description of traditional means of transportation in Kerinci Regency, Jambi Province.